Dual system - Deissinger, Thomas [Verfasser] (My University, 2010)
The main focus of this article lies on the structural features and working principles of the dual system of initial vocational training in Germany. It consists of a traditional pattern of skill formation, which goes back to the medieval mode of apprenticeship training. This means that training is workplace-led and predominantly practical although there is a vocational school involved in the training process. In Germany, other traits, such as the vocational principle and a special kind of public regulation, define a learning culture which differs from most other countries, including England and Australia. Unlike in the UK or France, where they form a marginal sector within the vocational training systems, dual apprenticeships exist in nearly all branches of the German economy including the professions and parts of the civil service. In Denmark, the dual system has undergone a number of flexibility changes, including single-venue training in a vocational college and modularization. (BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; T 1.2 Historische Berufsbildungsforschung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.3.5 Australien, Ozeanien; Berufsausbildung; Duales System; Historische Entwicklung; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Schweiz; Dänemark; England; Australien